The Effect of Healthy Phone-Call as Nutrition Management in Preventing Chronic Diseases - Nurhesti, P.O.Y.; Prapti, N.K.G.; Tirtayasa, K. (Journal of A Sustainable Global South; Vol 1 No 1 (2017): February 2017DO - 10.24843/jsgs.2017.v01.i01.p01, 2020)
Based on basic health research in 2007, chronic disease is still in the top ten of the most occurred in Indonesia. From the health profile  of Bali province  in  2014, it  shown  that the chronic disease is still in the top ten of most visit in the hospitals, both in inpatient  and outpatient. Bali province  is one of province with high density population.  The role of paramedic  in curing the chronic disease can be in the form of primary,  secondary,  or tertiary prevention.  Primary prevention for the chronic disease is conducted  through modifying  the risk factors via life style's  change. The healthy phone-call  method  is based on the culture of Balinese  community,  in which they are very consumptive  to use the communication  technology,  namely phone.  Individual who has been screened to have risks of having the contagious disease is monitored by paramedics  and get the needed medical services through  long distance  communication.  Many  controls  are needed  namely  regular  exercise,  knowledge  of healthy  food,  stress management. Telenursing method has several advantage, i.e., effective and efficient, lowering the curing cost of chronic diseases, and increasing the degree of the community health.  The aim of this study was to know the effect of healthy phone-call  to control the  risk  factor  of chronic  disease  in Bali.    The  research  method  used  was  quasy  experimental  to  analyse  the  difference  in knowledge,  attitude,  and behavior  of preventing  chronic disease  from nutrition  management  aspect in  individual  who has been screened to have chronic disease's  risk before and after the healthy phone-call  treatment.   This study was conducted  in working area of the Centre of Community Health III South Denpasar.  Individual with chronic disease's risk was given intervention namely phone-call  and short message three times per week for 3  weeks.  The results of this study demonstrated  a significant difference in chronic disease preventing  behavior based on nutrition management  aspect before and after given phone-call  on 30  respondents (p = 0,000).   A healthy phone-call  can be used  as one of chronic  disease primary prevention  method  through  knowledge  and information addition  in individual with chronic disease's risk. Chronic disease can be applied  in nursing nurturing treatment  in preventing and promoting efforts both in community and in hospital. Keywords:   Healthy phone-call, chronic disease prevention, nutrition management